Tren Penelitian Intervensi Nutrisi dalam Pencegahan Stunting: Studi Bibliometrik dari Basis Data Scopus - Nazar, Lailatun; Hasibuan, Rachma; Aliyah, Rifatul; Rahmawati, Dina; Ayu Ratnaningsih, Hanifa (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Stunting is a chronic form of malnutrition that has been a global public health issue for many years, with serious consequences on the physical growth, cognitive development and productive capacity of individuals. However, to date, there is no comprehensive map of research trends focusing on nutritional interventions to prevent this condition. This study aims to evaluate scientific advances in the field of nutritional interventions aimed at preventing stunting in children, indexed in the Scopus database between 2016 and 2025. The method used was quantitative bibliometric analysis, which consists of four steps: identification, screening, eligibility and inclusion. The study included publication volume per year, citations, h and g indexes, collaboration between authors and between countries, and keyword mapping using network and density visualization techniques. The results show an upward trend in the number of publications in 2017 and 2022, with the United States and Australia as major contributors and significant international collaboration. Key highly cited publications highlighted the effectiveness of breastfeeding education interventions, micronutrient supplementation and integrated nutrition farming interventions. Keyword visualization identified a major focus on “human, stunting, malnutrition” and the emergence of new themes such as “child health” and “eating behaviour”. In conclusion, nutrition intervention research trends for stunting prevention show significant growth and an evolving thematic focus, so these bibliometric results can serve as a reference for academics and policy makers to determine research priorities and more targeted and effective nutrition intervention strategies.